Republic of the Marshall Islands : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of the Marshall Islands. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlight that growth in the Marshallese economy is estimated to have accelerated to about 3.5 percent in FY2017 (ending September 30) with a strong pick-up in fisheries and construction, with the latter owing to the resumption of infrastructure projects. Consumer prices started to rise again in mid-2017, with annual consumer price index inflation at 1.1 percent in 2017Q4. Growth is expected to remain robust at about 2.5 percent in FY2018 and about 1.5 percent over the medium term, underpinned by further increases in infrastructure spending. Inflation is expected to rise gradually to about 2 percent over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet